Profiling academic research on discourse studies and second language learning - Castañeda, Harold (Colombian Applied Linguistics Journal, 2012)
There is little profiling academic research on discourse studies in relation to second language learning from a regional perspective. This study aims at unveiling what, when, where and who constitute scholarly work in research about these two interrelated fields. A dataset was configured from registers taken from Dialnet and studied using specialized text-mining software. Findings revealed myriad research interests, few prolific years and the lack of networking. It is recommended to trace out our research as an ELT community locally and globally.